The Community Participation in the Development of Gunung Salak Tourism Village, Tabanan, Bali, Indonesia - I Ketut Suarta; I Nyoman Meirejeki; I Ketut Suja; Ruju Rahmad; I Gusti Bagus Rai Utama (Lasigo Akademia Indonesia, 2022)
Gunung Salak Village Tabanan has the potential to attract natural tourism, customs, arts, and culture based on Hinduism, and is a strong potential to support its development into a Tourism Village. The development of Gunung Salak Tourism Village aims to improve the economy and advance the quality of life of the community. Data were collected through observation and interviews with purposive sampling method involving village leaders and Gunung Salak Village officials, namely Perbekel, Bendesa Adat, Kelian Dinas, Kelian Adat, BPD, Pokdarwis, and Head of BUMDes The collected data were tabulated and validated through Focus Group Discussion for further analyzed by qualitative descriptive. The results showed that the level of community participation was very good at the partnership level (level 6) where the position of the village government and the community became equal in authority and responsibility. It can be seen that participation is following Arnstein's characteristics, namely: initiation of submission of ideas and proposals from the community which is carried out in stages through Banjar institutions through customary and service groups. planning is still being assisted by another party, namely the Bali State Polytechnic, the power-sharing structure is carried out through Pokdarwis with Bumdes. While the forms of participation include the dimensions of thought, the dimensions of energy, and the dimensions of matter. Suggestions that can be submitted are that the village still needs assistance from the university for human resources training and determining the concept of developing the Gunung Salak Tourism Village based on local potential.